Research on Power Quality and Generator Core Loss base on the Stability of Wind Turbine Operation - Xin Guan; Chenhao Zhao; Yu Hua; Haoran Xu; Chuanbao Liu (Journal of Applied Science and Engineering, 2025)
Along with the gradual increase in the installed capacity of wind turbines, the length of wind turbine blades, as the main component for absorbing wind energy, has also increased. In the operation process of wind turbine, the blades will lead to impeller mass imbalance due to manufacturing or operation faults, resulting in affecting its output power quality. To clarify the changes of output power quality when impeller mass imbalance is occurred, in this paper, Maxwell, Simplorer, Simulink joint simulation calculation is used to study the influence of doubly-fed wind turbine on its output energy characteristic parameters when the impeller mass is unbalanced.The MMUSIC algorithm is utilized to extract the characteristic frequency of stator-rot or current for different impeller balance degrees. The results show that the generator stator and rotor current waveforms and generator core loss degree change when the impeller is in unbalanced state, so that the study of generator energy characteristic parameters can judge the operation imbalance of the wind turbine, so as to guarantee the operation reliability of the wind turbine and avoid the operation loss of the wind power enterprise in the operation process.